Perspectives on healthcare decarbonization through plant-rich dietary shifts: cases from the US, Austria and Taiwan - Wyma, Nanine; Niesing, Christi (Frontiers in Sustainable Food Systems, 2024)
The reduction of meat consumption in health systems is a high-impact pathway for healthcare decarbonization. Effects including changes in greenhouse gas emissions are rarely calculated following interventions, such as the implementation of plant-forward menus in hospitals, and the results of these changes are rarely published in peer-reviewed literature. In this perspective, we discuss the decarbonization outcomes of plant-rich dietary shifts across five health systems worldwide, gathered from peer-reviewed and gray literature. In each case, the implementation of a plant-rich approach reduced food-related greenhouse gas emissions. Health co-benefits are also commonly reported. The measurement of greenhouse gas emissions of plant-rich dietary shifts in future health system interventions is encouraged, with the results published in peer-reviewed journals.